Development of Project Based Learning (PjBL)-Based E-LKPD Assisted by the Canva Application on Human Digestive System Material in Class VIII of Middle School - Korompis Meggi Leddy Meylan; Jovialine Albertine Rungkat; Ferny Margo Tumbel; Orbanus Naharia; Zusje Wisye Merry Warouw (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The Student Worksheets (LKPD) used in schools are currently still dominated by conventional formats that are printed, procedural, and monotonous, so that students are less motivated in learning the complex and abstract material of the Human Digestive System. This study aims to describe the development process, as well as analyze the level of validity, practicality, and effectiveness of Project Based Learning (PjBL)-based E-LKPD products assisted by the Canva application on the Human Digestive System material in grade VIII of junior high school. This research method is a research and development (Research and Development/R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The trial subjects involved media experts, material experts, 2 science teachers, and grade VIII students of Koha Christian Junior High School. Results: The results of the validation of media experts and material experts at the final stage showed a media expert validation percentage of 90.00% and a material expert validation of 89.00% which is in the valid category and is suitable for use without revision. The practicality test of the product based on teacher responses obtained an average percentage of 89% and student responses reached 82%, both of which are included in the very practical category. The effectiveness test using N-Gain analysis of the pretest and posttest values ​​showed an average value of 0.4187 (41.87%) which is included in the moderate category. Conclusion: The PjBL-based E-LKPD assisted by the Canva application developed was proven to be valid, very practical, and quite effective in improving the cognitive abilities and learning outcomes of grade VIII junior high school students on the Human Digestive System material. Keywords: E-LKPD, Project Based Learning (PjBL), Canva, Human Digestive System